Coordination of carbon assimilation, allocation, and utilization for systemic improvement of cereal yield - Xiao-Gui Liang; Xiao-Gui Liang; Xiao-Gui Liang; Zhen Gao; Xiao-Xiang Fu; Xian-Min Chen; Si Shen; Shun-Li Zhou (Frontiers in Plant Science, 2023)
The growth of yield outputs is dwindling after the first green revolution, which cannot meet the demand for the projected population increase by the mid-century, especially with the constant threat from extreme climates. Cereal yield requires carbon (C) assimilation in the source for subsequent allocation and utilization in the sink. However, whether the source or sink limits yield improvement, a crucial question for strategic orientation in future breeding and cultivation, is still under debate. To narrow the knowledge gap and capture the progress, we focus on maize, rice, and wheat by briefly reviewing recent advances in yield improvement by modulation of i) leaf photosynthesis; ii) primary C allocation, phloem loading, and unloading; iii) C utilization and grain storage; and iv) systemic sugar signals (e.g., trehalose 6-phosphate). We highlight strategies for optimizing C allocation and utilization to coordinate the source–sink relationships and promote yields. Finally, based on the understanding of these physiological mechanisms, we envisage a future scenery of “smart crop” consisting of flexible coordination of plant C economy, with the goal of yield improvement and resilience in the field population of cereals crops.